Studi Kualitatif tentang Faktor-Faktor yang Memengaruhi Kepuasan Kerja Dosen - Riswandi, Riswandi; Puji Yuniarti; Iwan Asmadi; Zahra, Zahra; Andy, Andy (Yayasan Literasi Sains Indonesia, 2025)
The success of a higher education institution is largely determined by its human resources-namely, qualified lecturers and education staff who possess loyalty, dedication to their work, and a continuous desire to improve their competencies. As the main pillar of education, lecturers are responsible for the teaching and learning process, conducting research, and engaging in community service. Lecturer performance and job satisfaction are crucial in determining the quality of learning and education in higher education institutions. This study aims to examine and describe the various factors that influence lecturers' job satisfaction. Job satisfaction is affected by both internal and external factors. Internal factors include salary, benefits, workload, job autonomy, and opportunities for self-development. External factors include relationships with colleagues, leadership, organizational culture, and working conditions. The study was conducted over the course of one year using primary data collected through observations and interviews with respondents selected through purposive snowball sampling. Variables were measured using triangulation. Lecturers who are satisfied with their work tend to be more motivated, creative, and innovative in their teaching. High work motivation among lecturers also generates positive energy and dedication in carrying out their responsibilities as educators, ultimately contributing to the production of high-quality graduates.